Millimeter and X-Ray Emission from the 5 July 2012 Solar Flare - Ryzhov V.; Tsap Y.; Smirnova V.; Motorina G.; Morgachev A.; Kuznetsov S.; Nagnibeda V. (Springer Netherlands, 2022)
The 5 July 2012 solar flare SOL2012-07-05T11:44 (11:39 – 11:49 UT) with an increasing millimeter spectrum between 93 and 140 GHz is considered. We use space and ground-based observations in X-ray, extreme ultraviolet, microwave, and millimeter wave ranges obtained with the Reuven Ramaty High-Energy Solar Spectroscopic Imager, Solar Dynamics Observatory (SDO), Geostationary Operational Environmental Satellite, Radio Solar Telescope Network, and Bauman Moscow State Technical University millimeter radio telescope RT-7.5. The main parameters of thermal and accelerated electrons were determined through X-ray spectral fitting assuming the homogeneous thermal source and thick-target model. From the data of the Atmospheric Imaging Assembly/SDO and differential-emission-measure calculations it is shown that the thermal coronal plasma gives a negligible contribution to the millimeter flare emission. Model calculations suggest that the observed increase of millimeter spectral flux with frequency is determined by gyrosynchrotron emission of high-energy (≳300 ≳300  keV) electrons in the chromosphere. The consequences of the results are discussed in the light of the flare-energy-release mechanisms.